2015
DOI: 10.1016/j.otsr.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Severe slipped capital femoral epiphysis: A French multicenter study of 186 cases performed by the SoFOP

Abstract: The results of this study confirm the diverse nature of SCFE treatments available and the variability of their results. When selecting a treatment for severe SCFE, the goal is to stop the slip and also to prevent osteoarthritis by correcting the hip deformities. The "anterior" Dunn procedure was able to achieve these two goals, while having a lower complication rate than the other reduction techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
1
12
0
3
Order By: Relevance
“…Loder showed that AVN developed in 47% of unstable slips but none of the stable hips. This finding has been replicated by others [ 3 6 , 71 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Loder showed that AVN developed in 47% of unstable slips but none of the stable hips. This finding has been replicated by others [ 3 6 , 71 ].…”
Section: Discussionsupporting
confidence: 80%
“…Six studies (324 hips) provided useful data on the rate of FAI [ 43 , 46 , 57 , 58 , 70 , 71 ]. These studies investigated pinning in situ, physeal osteotomy and Ganz surgical dislocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to previous reports, which showed that a severe slip has a higher percentage of AVN. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…A multi-centre French study concluded that prevention of AVN, osteoarthritis (OA) and FAI should be considered as the goal of treatment by using the anterior Dunn procedure for severe slips. 5 In the SCFE-affected hip, the presence of FAI causes mechanical abnormalities that can lead to osteoarthritis due to repetitive injury to the articular cartilage. Considering this situation, preventing impingement is preferable, rather than treating it later.…”
Section: Introductionmentioning
confidence: 99%